PENENTUAN RASIO DAN DURASI MATRICONDITIONING DENGAN VERMICOMPOST UNTUK MENINGKATKAN MUTU BENIH KEDELAI (Glycine max L. Merr.) - Permatasari, Dewi Rahmawati Intan; Sari, Siti Mardhika; Aziez, Achmad Fatchul; Supriyadi, Teguh; Priyadi, Sapto; Damayanti, Adhisty Puri (Jurnal Ilmiah Hijau Cendekia, 2025)
The rapid deterioration of soybean seeds during storage severely limits the availability of high-quality planting stock. Seed invigoration, specifically through matriconditioning, a technique involving controlled hydration using a moist solid medium, offers a method to improve the germination capacity of aged seeds. This study was thus designed to ascertain the optimal dosage of vermicompost utilization as a matriconditioning agent for improving the physiological quality of soybean seeds. Vermicompost, the product of organic matter decomposition, provides a comprehensive nutrient profile that may enhance seed physiological quality. The research aimed to determine the optimal vermicompost dosage for improving soybean seed physiological quality. A two-factor Factorial Completely Randomized Design (CRD) with four replications was employed. The factors were the priming ratio seed (g): vermicompost (g): water (ml) at four levels R0​ (control), R1​ (12:14:12), R2​ (12:14:13), R3​ (12:14:14) and priming duration four levels: D0​ (control), D1​ (6 hours), D2​ (12 hours), D3​ (18 hours). The experiment used Argomulyo cultivar seeds (initial germination 70-79%). Results indicated that the most effective invigoration treatment utilized the vermicompost priming ratio of 12:14:12 and an incubation period of 18 hours at ambient conditions (25±2 ºC).